The impacts of genotype and harvest time on dry matter, biogas and methane yields of maize (Zea mays L.) - Tatah , Eugene Lendzemo; Justus Liebig University Giessen (My University, 2008)
This research was set up to select maize cultivars and appropriate harvest times to harvest for optimum dry matter, biogas and methane yields in Gießen and Groß-Gerau.

Der Versuch wurde in Gießen und Groß-Gerau durchgeführt um Maissorten und geeignete Erntetermine zur Optimierung von Trockenmasse, Biogas- und Methanertrag.
Der Einfluss des genotyps und des Erntezeitpunktes auf Trockenmasse, Biogas- und Methanerträge von Mais (Zea mays L.)
Keywords: Mais; Biogas; Methan; Erntezeitpunkt; Sorten; Maize; biogas; methane; harvest time; cultivars; ddc:630